Cellulose-Based Materials for Water Remediation: Adsorption, Catalysis, and Antifouling - Abdelhamid, Hani Nasser; Mathew, Aji P. (Frontiers in Chemical Engineering, 2021)
Cellulose-based materials have been advanced technologies used in water remediation. They exhibit several advantages being the most abundant biopolymer in nature, high biocompatibility and contain several functional groups. Cellulose can be prepared in several derivatives including nanomaterials such as cellulose nanocrystals (CNCs) and cellulose nanofibers with functional groups. The presence of functional groups such as carboxylic and hydroxyls groups can be modified or grafted with organic moieties offering extra functional groups customizing for specific targets. These functional groups ensure the capability of cellulose biopolymers to be modified with nanoparticles such as metal-organic frameworks (MOFs), graphene oxide (GO), silver nanoparticles, and zinc oxide nanoparticles. Thus, they can be applied for water remediation via removing water pollutants such as heavy metal ions, organic dyes, drugs, and microbial species. Cellulose-based materials can be also used for removing microorganisms being active as membranes or antibacterial agents. They can proceed into various forms such as membranes, sheets, papers, foams, aerogels, and filters. This review summarized the applications of cellulose-based materials for water remediation via adsorption, catalysis, and antifouling. The high performance of cellulose-based materials as well as their simple processing methods ensure the high potential for water remediation.